A REVIEW OF MODELS AND THEORETICAL PERSPECTIVES TO STUDY OF PROFESSIONAL BURNOUT - Gil Monte, Pedro R.; Peiró, José María (Anales de Psicología / Annals of Psychology, 1999)
This paper justifies the convenience of studying the burnout syndrome. Taking into consideration a psychosocial orientation, the burnout syndrome is shown as a process that integrates cognitive/aptitudinal (i.e., low personal accomplishment), emotional (i.e., emotional exhaustion), and attitudinal (i.e., depersonalization) components. Based on this conceptualization, we offer a taxonomy to integrate the principal models proposed in literature to explain the causes and consequences of burnout. This taxonomy offers three groups of models. The first group integrates models elaborate considering an individual approach to study burnout. A second group integrates models elaborate from interpersonal approachs (i.e., social exchange theories), and the third group includes models elaborate from organizational approachs. In a second section, we offer the results obtained for our research team considering variables from every perspective show above, and lastly the paper concludes with suggestions for future research.